Influence of the recyclate content of silicone elastomers on the mechanical properties of high consistency silicone rubber - Timo Hofmann; Kevin Klier; Ralf- Urs Giesen; Hans- Peter Heim (Polymer Testing, 2025)
In this publication, the effects of finely ground silicone elastomer recyclate powder (>50 μm) as a filler in a solid silicone rubber were investigated. The results indicated that when peroxide-curing high consistency silicone rubber is used, the recycled material has no influence on the crosslinking. In the rheological tests, however, it was observed that the viscosity increases with increasing filler content. The present study analyzed the tensile test and compression set to reveal an influence on the elastic properties of the material. The compression set increases by approx. 22 % compared to the reference value up to 60 phr recyclate content. In terms of tensile strength, the recyclate leads to a decrease in maximum stress of up to 45 % and elongation of up to 25 %. In contrast to the elastic properties, however, no significant change in hardness can be seen as a result of using the recycled powder.